PENGARUH MEDIA AUDIOVISUAL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA DI SDN 3 AMPANA KOTA - Nurafni Khairunnisa; Rusdin; Arda (Koordinat Jurnal MIPA, 2022)
This research aims to determine effect of audiovisual media in improving student learning outcomes in science learning at SDN 3 Ampana City, Tojo Una-una Regency on theme 9 "Exploring Outer Space". This research is descriptive quantitative with with one group pretest-posttest design. The research sample was 27 students of class VI. Data collection was carried out through written test using multiple choice question. The results of the research indicate the influence of audiovisual media in improving student learning outcomes. This is evidenced by the average results of the pretest of 38.52 and the posttest of 73.70. This result is higher than the KKM 70. Runs test in the posttest obtained a value of 0.101 with a significance level of 5% (0.05), which means that H0 is rejected and H1 is accepted.